The Effectiveness of an Anti-Bullying Program on Academic Hope in Elementary School Students - Badri, Rahman; Mehr, Akram Aria (South Sulawesi Education Development, 2025)
Bullying in schools has negative consequences on students' mental health and academic performance. This study aimed to examine the effectiveness of the anti-bullying program on the academic hope of elementary school students. The study employed a quasi-experimental pretest-posttest design with a control group. This design was chosen due to ethical and practical constraints in randomizing schools. The statistical population included all sixth-grade students in Ahar city (N=3,829) in 2025. A sample of 40 students was selected through cluster random sampling and assigned to experimental and control groups (20 students each). The experimental group participated in the anti-bullying program for 15 sessions (45 minutes each). Data were collected using the Academic Hope Scale, which demonstrated good reliability (α=0.87 for the full scale, α=0.82 for the